Novel bi-allelic DNAH3 variants cause oligoasthenoteratozoospermia - Li, Shu; Zhang, Zexin; Xie, Linna; Zhao, Yanqiu; Chen, Hongtai; Zhang, Shijia; Cai, Yixiang; Ren, Bingjie; Liu, Wensheng; Tang, Songxi; Sha, Yanwei (Frontiers in Endocrinology, 2024)
Background: Oligoasthenoteratozoospermia (OAT), is a widespread cause of male infertility. As one of the usual clinical manifestations of OAT, multiple morphological abnormalities of the sperm flagella (MMAF) is involved frequently mutations and defects of the dynein family, However, the relationship between the newly identified DNAH3 mutation and oligonasthenospermia in humans has not been established. Methods: Two patients from different unrelated families with DNAH3 mutation were performed by whole exome sequencing, pathogenicity analysis, and species conservation analysis of mutation sites. We predicted the representative sites after mutation and predicted the protein structure. The sperm characteristics of two patients with DNAH3 mutations were verified by Papanicolaou staining, scanning electron microscopy, and transmission electron microscopy, as well as mRNA and protein levels by RT-qPCR and Western blotting. Results: The biallelic mutation of the first progenitor was c.6535_6536 delinsAC heterozygote deletion to infect mutation (p.Asp2179Thr) and stop codon premutation C.10249G > A (p. Trp3420ter). In family II, the patient (P2) harboured a DNAH3 heterozygous missense mutation c. 10439G> a (p.RG3480gln) and a stop codon premutation C.10260g > A (p.rp3420ter), Patients with premature termination of transcription translation by DNAH3 mutations exhibit OAT phenotypes, such as fibrous sheath dysplasia and multiple tail malformations. We predicted the representative sites after mutation, predicted the protein structure, and detected changes in the protein levels of DNAH3 and related genes after mutation, especially the significant deletion of DNAH3 on immunofluorescence staining in patients. We may explore in the future how DNAH3 affects sperm motility and quality through regulatory mechanisms of protein structural changes. Conclusion Novel DNAH3 biallelic mutations, especially the premature appearance of the stop codon, may have changes in protein expression, structure, and active site, lead to spermatogenic failure, even induce OAT. The discovery of new mutations in DNAH3 may be the key to the diagnosis and treatment of OAT.